Financial and Macroeconomic Ratio Analysis Against Financial Distress - Ariefah, Nuraini; Hirdinis, Hirdinis (Universitas Mercu Buana, 2025)
This study aims to analyze the effect of financial ratios and macroeconomic factors on financial distress in trade, service and investment sector companies during the 2018-2021 period. The sampling method used a purposive sampling technique with a total sample of 58 companies. Testing was carried out using E-Views using the panel data regression analysis method. Financial distress is measured using the Altman Z-Score where the higher the value indicates the healthier the company. The results showed that the profitability ratios as measured by Return on Assets had a significant positive effect on financial distress. That is, the higher the Return on Assets, the healthier the company's finances. The leverage ratio as measured by the Debt-to-Equity Ratio has no significant effect on financial distress. The liquidity ratio as measured by the Current Ratio has a significant positive effect on financial distress. In addition, the activity ratio as measured by Total Asset Turnover has a significant negative effect on financial distress. That is, the higher the total asset turnover of a company, the more un-healthy the company's financial condition will be. The inflation variable as measured by the Consumer Price Index has no significant effect on financial distress in companies in the trade, service and investment sectors during the 2018-2021 period.